Topical arginase inhibition decreases growth of cutaneous squamous cell carcinoma - Amit Mittal (Nature Portfolio, 2021)
Abstract Cutaneous squamous cell carcinomas (cSCC) are among the most commonly diagnosed malignancies, causing significant morbidity and mortality. Tumor-associated macrophage (TAM) expression of arginase is implicated in tumor progression, and therapeutic use of arginase inhibitors has been studied in various cancers. However, investigating potential cSCC immunotherapies including arginase inhibition in pre-clinical models is hampered by the lack of appropriate tumor models in immunocompetent mice. PDV is a cSCC cell line derived from chemical carcinogenesis of mouse keratinocytes. PDVC57 cells were derived from a PDV tumor in C57BL/6 (B6) mice. Unlike PDV, PDVC57 tumors grow consistently in B6 mice, and have increased TAMs, decreased dendritic and T cell intra-tumor infiltration. Arginase inhibition in cSCC tumors using Nω-hydroxy-nor-arginine (nor-NOHA) reduced tumor growth in B6 mice but not immunodeficient Rag1-deficient mice. nor-NOHA administration increased dendritic and T cell tumor-infiltration and PD-1 expression. The combination of nor-NOHA and anti-PD-1 therapy with nivolumab enhanced anti-PD-1 therapeutic efficacy. This study demonstrates the therapeutic potential of transcutaneous arginase inhibition in cSCC. A competent immune microenvironment is required for tumor growth inhibition using this arginase inhibitor. Synergistic co-inhibition of tumor growth in these results, supports further examination of transcutaneous arginase inhibition as a therapeutic modality for cSCC.